Conversion Efficiency of Electromagnetic Radiation in the Vacuum Diode - Makaryan, A. N.
In this paper, we consider the efficiency of conversion of electromagnetic radiation in its nonlinear interaction with the space charge of a flat vacuum diode, depending on the radiation intensity and on the applied constant electric field. It is shown that the detected signal and the amplitude of the second harmonic field, as well as the conversion efficiency increase with an increase in the amplitude of the electromagnetic radiation field. The conversion efficiency can be improved by an optimal choice of the bias field, as well as by increasing the area of interaction of the electromagnetic wave with the space charge.
Keywords: Physics; Electronics; Electromagnetism; electron and ion optics; Direct energy conversion and storage